Penerapan Fidget Spinner pada Anak 13-18 Tahun dengan Fraktur untuk Mengurangi Nyeri Pasca Operasi - M. Weny Puji Atmani; Ketut Suryani (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Background: Adolescent development includes physical, social, emotional, cognitive and psychosocial. Adolescents are easily emotional, enjoy challenging things, act impulsively, pay little attention to personal safety so there is a risk of physical injury and falls, which can result in fractures. Fracture treatment is surgery. The impact of surgery is pain, pain management can be done by playing fidget spinner therapy. A fidget spinner is a toy that rotates between two fingers, in the shape of a propeller with a ball bearing in the middle, creating a stunning rotating pattern, unique design, attracting children and reducing pain. Objective: Fidget spinner play therapy is applied to reduce pain intensity in children aged 13-18 years. Method: The research method is a case study with 3 respondents who experienced post-operative fractures using a fidget spinner and the Wong Baker pain scale. Results: The results for respondents 1, 2 and 3 showed a decrease in pain intensity, the average pre test for respondent 1 had pain 4 and the average post test pain was 3. Respondent 2 had an average pre test pain scale of 4 and post test pain scale 2. For respondent 3, the average pre test pain scale was 5 and post test 3. Conclusion: The application of fidget spinner play therapy is effective in reducing pain in children with post-operative fractures. Suggestion: This application is expected to be used in nursing care for children with post-operative fractures on the second day.